The new Hegelians politics and philosophy in the Hegelian school - Moggach, Douglas (Cambridge University Press, 2006)
The period leading up to the Revolutions of 1848 was a seminal moment in the history of political thought, demarcating the ideological currents and defining the problems of freedom and social cohesion which are among the key issues of modern politics. This 2006 anthology offers research on Hegel's followers in the 1830s and 1840s. With essays by philosophers, political scientists, and historians from Europe and North America, it pays special attention to questions of state power, the economy, poverty, and labour, as well as to ideas on freedom. The book examines the political and social thought of Eduard Gans, Ludwig Feuerbach, Max Stirner, Bruno and Edgar Bauer, the young Engels, and Marx. It places them in the context of Hegel's philosophy, the Enlightenment, Kant, the French Revolution, industrialization, and urban poverty. It also views Marx and Engels in relation to their contemporaries and interlocutors in the Hegelian school
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Hegel, Georg Wilhelm Friedrich / 1770-1831; Hegel, Georg Wilhelm Friedrich / 1770-1831 / Influence; Hegel, Georg Wilhelm Friedrich -- 1770-1831; Geschichte 1800-1900; Geschichte 1830-1840; Politik; Philosophy, German / 19th century; Hegelianismus; Neuhegelianismus; Politische Philosophie; Linkshegelianer; Deutschland; Germany / Politics and government / 1806-1848; Aufsatzsammlung